(untitled) (Revista Apotheke, 2022)
This paper discusses micropolitics in contemporary art through a performance art entitled: “Letters to a closet”. The research analyzes letters (narratives) of experiences that mark the bodies of students/teachers of art in an academic context of a degree course in Visual Arts. This is a qualitative study and its method is Cartography. To discuss the aspects that permeate the performance, the object of this study, we discuss the concepts of micropolitics, experience and the relationship between narratives and memory. Our aim is to understand the relationship between art and politics in the micropolitical context of a performance art with art students/teachers in a degree course in Visual Arts. The letters highlight themes biased with the problems existing in contemporary society and present experiences that cross the life of minority and marginalized groups in capitalist society. We believe this study contributes to the understanding of the relationships established between art and life; creative potential in institutional spaces; integration of themes related to social agendas through art and evidences potency for the formation of art teachers.